Utilização de resíduos dregs da indústria de papel e celulose para a produção de ligantes álcali-ativados - Oliveira, Cecilia Prado (2023)
The pulp and paper industry stands out for its worldwide production. However, roughly 88 kg of solid waste are generated per ton of paper produced, from which 4 to 20 kg are green liquor dregs derived from the chemical recovery cycle in the kraft pulping process. The present study evaluates the use of green liquor dregs to produce metakaolin-based alkali-activated binders. The residues were thermally treated to obtain reactive calcium oxide, which is known for its porosity-reducing effects in alkali-activated materials. It was determined by thermal and statistical analysis that calcination at 915 ºC for 2 h causes decarbonation of calcite in the residues. Green liquor dregs calcined at these conditions were characterized by thermogravimetry analysis, X-ray fluorescence, X-ray diffraction and laser granulometry. The results suggest that thermal treatment was efficient in terms of CaO formation and loss on ignition reduction. The evaluation of binders produced with thermally treated green liquor dregs was based on a central composite design that considered three variables: the mass ratio of activator/precursor; curing time; and metakaolin substitution percentage for thermally treated dregs. Tests of mini-slump, compression, ultrasonic wave transmission, determination of length change and infrared spectroscopy were conducted. By response surface methodology, it was determined that increasing activator/precursor ratio and percentage of dregs causes an increase in the spread of pastes and a decrease in its compressive strength and dynamic modulus of elasticity. However, it is noteworthy that the compressive strength of all mixtures was superior to 20 MPa at 3 days and 25 MPa at 7 days. Also, the decrease in strength ranged between 1.16 and 3.33 MPa when increasing GLD percentage from 4,05 to 15,95% in mixtures with activator/precursor mass ratio of 0.54 and 0.66. These factors indicate that using green liquor dregs to produce alkali-activated binders is feasible, if associated with proper formulations.